Legal Personality of Rivers in Bangladesh and India - Siddiki, Umar Faruque; Tuli, Tamanna Aziz (Law and Policy Review, 2024)
The emerging scholarship of river personification, which envisions rivers as a subject of law, arguably leads to a theoretical and legal reconceptualisation of the predominant human–nature binary (Hutchison, 2014). This paper aims to delve into the theoretical underpinning of the legal personality of rivers in light of some recent judicial decisions declared by the courts in Bangladesh and India. The paper begins with a discussion of a judgement by the High Court Division of the Supreme Court of Bangladesh that has conferred legal personality to all the rivers in Bangladesh (Human Rights & Peace for Bangladesh vs Bangladesh, 2019). It then draws a comparative study with the decision of the Uttarakhand High Court on the legal personality of the rivers Ganges and Yamuna. Furthermore, the paper examines the current trend of personifying rivers to understand how this new trend initiates a different understanding of the river and contributes to shifting the rivers’ right paradigm from anthropocentrism to ecocentrism. The study critically engages with anthropocentrism and argues that a purely anthropocentric framework is insufficient to understand the issues facing rivers in Bangladesh today.